Fabrication and characterization of methylammonium lead iodide-based perovskite solar cells under ambient conditions - Dwayne Jensen Reddy; Ian Joseph Lazarus (Institute of Advanced Engineering and Science, 2024)
This study investigated the fabrication and characterization of CH3NH3PbI3 based perovskite solar cells (PSCs) using the one-step spin coating technique under ambient conditions, eliminating the need for expensive glovebox and thermal evaporation equipment. The perovskite layer was annealed at 65 °C for 30 seconds and 100 °C for 30 seconds, 1 and 2 minutes. The scanning electron microscope (SEM) images show a smooth and uniform surface coverage for the ETL and CH3NH3PbI3 layers. SEM results also show an average grain size of 397 nm for CH3NH3PbI3 and an average particle size of 17 nm for TiO2 was confirmed by transmission electron microscopy (TEM). X-ray diffraction (XRD) results confirmed the formation of tetragonal perovskite (CH3NH3PbI3) phase with high crystallinity with a crystallite size of 19.99 nm for the samples annealed for 30 seconds at 65 °C and 1 min at 100 °C. FTIR results also confirmed the presence of anatase TiO2 at wavenumber 438 cm-1 and the formation of the adduct of Pb2 with dimethyl sulfoxide (DMSO) and MAI is confirmed at 1,015 cm-1 . From the Tauc plot the bandgap energy of TiO2 and Perovskite layers was determined to be 3.52 eV and 2.06 eV respectively. An open-circuit voltage was 0.9057 V and short circuit current density was 12.2185 mA/cm2 with a fill factor of 48.05 and power conversion efficiency (PCE) of 5.199%.